The impact of the State Migration Centre on the current and future economic Well-Being of Western Australia - A Review. - Stromback, Carl; Mahendran, Anusha; Mazzarol, T. (Centre for Labour Market Research, 2008)
The connection between immigration and skill shortages has a long and illustrious history. This report reviews the role and performance of the State Migration Centre (SMC) in meeting this need and develops a strategy for its future operations. The starting point is a conceptual overview of the economic case for the continuing need for trained and competent workers from abroad. The outcome of this overview is a list of factors and considerations relevant to assessing the SMC performance. The body of the report then provides an overview of the recent trends in business and skilled migration and goes on to analyse of the SMC's role and performance. Its role is clarified by reference to the current immigration policy and recent trends in skilled and business migration. This provides the setting for an analysis of its performance drawing on the indicators developed in the first section of the report. Looking ahead to the future, we than consider the likely future needs as indicated by the demand for skilled workers, the extent to which this demand is met by the resident workforce and the migration planning levels. This analysis provides the basis for a range of options that the SMC might pursue. The funding levels associated with these options are outlined and a series of recommendations are put forward.